Woman Main Character Response to Nature Exploitation in Annihilation (2018): An Ecofeminist Study - Farhan Alibasjah (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2022)
Nature is used by humans for a variety of purposes, from exploration to exploitation. Gender issues are linearly aligned and appear to be almost identical. Within unequal power relationships that result in exploitation, women in this context are associated with nature and the environment, where they put in the effort to fight for nature's preservation. This study aims to find out how woman main character response to nature exploitation was found in Annihilation (2018) by Alex Garland. Furthermore, an analysis of two aspects of film studies was carried out, namely the cinematography and the script of the film. The Alex Garland film Annihilation (2018) was the study's data source. The process of watching, enlisting, and screenshotting was used to collect the data. The data were analyzed by identifying, classifying, and interpreting. This study uses the approach and theory of Tong's (2006) ecofeminism to find out how woman main character responses are represented through two forms in films, namely natural ecofeminism and socialist ecofeminism. The results of this study show several responses made by woman main character to safeguard nature, incorporating partaking in risky expeditions and facing enormous challenges to save the environment. However, there are also acts of exploitation in films that show women like man identity that are greedy, selfish, and harm others. Keywords: ecofeminist, woman main character response, nature exploitation.